Species limits in butterflies (Lepidoptera: Nymphalidae): reconciling classical taxonomy with the multispecies coalescent. (18th March 2019) - Matos‐Maraví, Pável; Wahlberg, Niklas; Antonelli, Alexandre; Penz, Carla M.
Abstract: Species delimitation is at the core of biological sciences. During the last decade, molecular‐based approaches have advanced the field by providing additional sources of evidence to classical, morphology‐based taxonomy. However, taxonomy has not yet fully embraced molecular species delimitation beyond threshold‐based, single‐gene approaches, and taxonomic knowledge is not commonly integrated into multilocus species delimitation models. Here we aim to bridge empirical data (taxonomic and genetic) with recently developed coalescent‐based species delimitation approaches. We use the multispecies coalescent model as implemented in two Bayesian methods (dissect/stacey andbp&p ) to infer species hypotheses. In both cases, we account for phylogenetic uncertainty (by not using any guide tree) and taxonomic uncertainty (by measuring the impact of using a priori taxonomic assignments to specimens). We focus on an entire Neotropical tribe of butterflies, the Haeterini (Nymphalidae: Satyrinae). We contrast divergent taxonomic opinion – splitting, lumping and misclassifying species – in the light of different phenotypic classifications proposed to date. Our results provide a solid background for the recognition of 22 species. The synergistic approach presented here overcomes limitations in both traditional taxonomy (e.g. by recognizing cryptic species) and molecular‐based methods (e.g. by recognizing structured populations, and not raising them to species). Our framework provides a step forward towards standardization and increasing reproducibility of species delimitations. Abstract : Molecular species delimitation using the multispecies coalescent model informed with taxonomic knowledge delineates traditionally viewed subspecies and species in the butterfly tribe Haeterini. A Bayesian species delimitation framework allowed the explicit incorporation of tree topology and taxonomic assignment uncertainties, which ameliorates potential biases in the estimation of speciation probabilities. Haeterini butterflies evolved for nearly 27 Ma, but most extant species ( c . 80%) probably diverged rather recently, within the past 2 Ma.